HCV Elimination in Central Europe with Particular Emphasis on Microelimination in Prisons - Flisiak, Robert; Zarębska-Michaluk, Dorota; Ciupkeviciene, Egle; Drazilova, Sylvia; Frankova, Sona; Grgurevic, Ivica; Hunyady, Bela; Jarcuska, Peter; Kupčinskas, Limas; Makara, Michael; Saulite-Vanaga, Gunita; Simonova, Marieta; et al. (Viruses, 2022)
In 2016, the WHO announced a plan to eliminate viral hepatitis as a public health threat by 2030. In this narrative review, experts from Bulgaria, Croatia, the Czech Republic, Hungary, Latvia, Lithuania, Poland and Slovakia assessed the feasibility of achieving the WHO 2030 target for HCV infections in Central Europe. They focused mainly on HCV micro-elimination in prisons, where the highest incidence of HCV infections is usually observed, and the impact of the COVID-19 pandemic on the detection and treatment of HCV infections. According to the presented estimates, almost 400,000 people remain infected with HCV in the analyzed countries. Interferon-free therapies are available ad libitum, but the number of patients treated annually in the last two years has halved compared to 2017-2019, mainly due to the COVID-19 pandemic. None of the countries analyzed had implemented a national HCV screening program or a prison screening program. The main reason is a lack of will at governmental and prison levels. None of the countries analyzed see any chance of meeting the WHO targets for removing viral hepatitis from the public threat list by 2030, unless barriers such as a lack of political will and a lack of screening programs are removed quickly.
Keywords: WHO; hepatitida C; Evropa; Europe; therapy; Pandemics; hepatitis; lidé; věznice; HCV; screening; pandemie; Humans; epidemiology; Hepatitis C; Prisons; COVID-19